BUSINESS PLAN KLASTER KERAJINAN KUNINGAN DILIHAT DARI ASPEK SOSIAL BUDAYA DI KECAMATAN JUWANA KABUPATEN PATI - Soebandriyo Soebandriyo; Etty Sugiarti (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2011)
Research target to analyse cultural social condition of entrepreneur of Industri minimice middle klaster of brass to compile business plan in Kecamatan Juwana Kabupaten Pati.. His population entire all brass worker which sum up his as much 80 effort unit of because of the limited resource taken by selected sampel research in purposif. Location in Kecamatan Juwana Kabupaten Pati, Items from culture social covering, technological appliance, economic system, family, and the political power. analysed descriptively qualitative. Conclusion, used technology still modestly , of most ommission from their parent first hereditaryly. And socialize Kecamatan Juwana of there no togetherness in obtaining raw material in the form of ex- brass, searching order to factory, even to Bank to look for capital. Society Kecamatan Juwana Doing cor of brass of executed to by existing labour usher family by self. Construction to socialize Kecamatan Juwana Moving cor brass of there no especially to open network look for order and marketing of yield up the ghost to factory still walk by self in compete.